Dynamics of Regional Finance and Economic Growth in Bali Province - Putra, I Putu Reza Krisna; Setyari, Ni Putu Wiwin (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2026)
This study focuses on examining the relationship between local government financial performance and its economic growth in Bali Province using panel data from nine regencies and cities over the period 2012–2024, covering a total of 117 observations. The dependent variable is region’s economic growth, whilst region’s fiscal independence (PAD share), region’s fiscal transfer dependency, region’s expenditure efficiency, and region’s capital expenditure are the independent variables. The Autoregressive Distributed Lag (ARDL) approach was employed to analyze both short-term and long-term dynamics, which was further verified by tests of stationarity, cointegration, and Dumitrescu–Hurlin causality. The findings indicate that region’s fiscal independence and expenditure efficiency are statistically significantly affect long-term economic growth. We also found that region’s fiscal transfer dependency and region’s capital expenditure are not statistically significant in the long run. However, in the short-run, only region’s capital expenditure has a positive effect on region’s economic growth. One important finding is that causality runs in a one-way from economic growth to transfer dependency. Hence, the policy implications highlight the importance of strengthening region’s own-source revenue, improving region’s spending efficiency, and enhancing the quality of capital expenditures to spur sustainable regional economic growth.